Multivariable & vector calculus - Maslan Osman; Yusof Yaacob (Penerbit Universiti Teknologi Malaysia, 2008)
This book is based on the lectures given by the authors to engineering students taking Engineering Mathematics in Universiti Teknologi Malaysia. The lecture notes have been rewritten so that the book is also suitable for science students studying multivariable and vector calculus in higher learning institutions.